Chinese internet buzzwords : research on network languages in internet group communication - Zhou, Yan, 1982- (Abingdon, Oxon ; New York : Routledge, 2022)
"As the Internet has reshaped the way we communicate, people's reading has become more fragmented and attention has been directed to a more concise and general form of language that outlines the most important information. This language of the internet, a language system that concentrates on the content of events and public emotions, has emerged and received wide currency. This monograph is one of the first books to examine the language of the internet in the Chinese context. By analysing content and discourse, the author examines Chinese website buzzwords since 2010. She reveals the mechanisms of generation, the cultural nature and political characteristics of the network language, analyzes the causes of its emergence and popularity, and highlights its social and academic significance. Meanwhile, she argues that research in the area is essentially interdisciplinary, involving not only perspectives from Journalism and Communication Studies, but also Philosophy, Culture, Linguistics and Sociology. Students and scholars of Communication Studies and Journalism, as well as Culture Studies should be greatly interested in this title"--
Overview of research on network language from the perspective of communication -- Network language in the era of group communication -- The network language user of combination of communicator and receiver -- Network language: an important representation of contemporary Chinese media culture -- Network language as a symbolic expression of network public opinions.
Includes index.
Keywords: Language and the Internet -- China; Mass media and language -- China; Online journalism -- China; Internet users -- China; LANGUAGE ARTS & DISCIPLINES / General; LANGUAGE ARTS & DISCIPLINES / Journalism; SOCIAL SCIENCE / Popular Culture